Liquid crystal polyester resin composition, liquid crystal polyester film, metal laminated film, and circuit board

By adding amorphous copolyester at a glass transition temperature of 80~200°C to the thermoplastic liquid crystal polyester, the problems of melt viscosity reduction and wrinkles in the blow molding and extrusion molding are solved, and stable and smooth film formation and excellent results are achieved. The mechanical and electrical properties are suitable for high-speed communication circuit boards.

CN119307075APending Publication Date: 2025-01-14OKURA INDUSTRIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410923132.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-12
Filing Date
2024-07-10
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the blow molding extrusion molding method, the existing thermoplastic liquid crystal polyester is prone to decrease in melt viscosity due to increased shear stress and temperature, making it difficult to form a film stably, and is prone to slack and wrinkles, affecting its mechanical and electrical properties.

Method used

By adding amorphous copolyester with a glass transition temperature of 80~200°C to the thermoplastic liquid crystal polyester, the dependence of melt viscosity on temperature and shear stress is reduced, the sliding properties are improved, and bubble shaking and wrinkle generation are suppressed. Form a stable smooth film.

Benefits of technology

It realizes the stable formation of a film without sagging and wrinkles in the blow molding extrusion forming method, maintains the excellent mechanical and electrical properties of the thermoplastic liquid crystal polyester, and is suitable for high-speed communication circuit boards and other uses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The purpose of the present invention is to provide a liquid crystal polyester resin composition, a liquid crystal polyester-based film, a metal laminated film, and a circuit board which are excellent in mechanical properties, electrical properties, and heat resistance, while suppressing the occurrence of slack and wrinkles in a film during extrusion molding such as a blow extrusion molding method, and which are capable of forming a stable film. A liquid crystal polyester-based resin composition containing a thermoplastic liquid crystal polyester (A) and an amorphous copolyester (B), characterized in that the amorphous copolyester (B) has a glass transition temperature of 90 DEG C or more and 200 DEG C or less, and the blending ratio of the thermoplastic liquid crystal polyester (A) to the amorphous copolyester is (A): (B) = 50-99 wt%: 1-50 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a liquid crystal polyester resin composition mainly composed of a thermoplastic liquid crystal polyester capable of forming an optically anisotropic melt phase, and also relates to a liquid crystal polyester film using the resin composition, and a metal laminate film and a circuit board using the film. Background Art

[0002] In recent years, in the field of electronics and electrical equipment, the demand for miniaturization and lightness of equipment has increased, and an insulating film with excellent electrical and mechanical properties is needed. However, the raw materials of current insulating films, such as polyimide and polyethylene terephthalate, have the following problems: the electrical properties in the high frequency band are insufficient, and the high hygroscopicity leads to poor electrical properties and large dimensional changes, making it difficult to achieve a film that meets the above requirements.

[0003] Thermoplastic liquid crystal polyesters have attracted much attention as materials for flexible printed circuit (FPC) substrates, etc., due to their excellent mechanical properties such as heat resistance and rigidity, chemical resistance, dimensional accuracy, etc., as well as excellent electrical properties (low dielectric constant, low dielectric loss tangent) in high frequency bands (GHz band) and low transmission loss in circuits.

[0004] Thermoplastic liquid crystal polyester can be formed into a film by various extrusion molding methods. However, as a film formed by T-die extrusion molding, since the molecules of thermoplastic liquid crystal polyester having a rigid molecular structure are easily oriented in the flow direction in a molten state, the orientation along the molecular chain in the stretching direction (MD direction) and the direction orthogonal thereto (TD direction) shows anisotropy, and it is difficult to obtain a thermoplastic liquid crystal polyester film in which the molecular chain orientation is isotropic.

[0005] In contrast, the blow extrusion molding method can stretch the molten thermoplastic liquid crystal polyester extruded from the annular die in both the MD and TD directions. Therefore, by appropriately adjusting the blowing ratio and controlling the orientation of the molecular chains, an isotropic thermoplastic liquid crystal polyester film can be easily obtained.

[0006] However, the melt viscosity of thermoplastic liquid crystal polyesters is largely dependent on shear stress and temperature, and has the characteristic that a slight increase in shear stress and temperature will lead to a significant decrease in melt viscosity. Therefore, when thermoplastic liquid crystal polyesters are melt-extruded by blow extrusion molding, there is a problem that the melt viscosity may drop sharply due to the shear stress generated in the die head part and the increase in temperature, making it difficult to maintain the shape of the bubbles and thus difficult to form a film stably.

[0007] Patent document 1 is an invention relating to a polymer alloy consisting of a thermoplastic polymer (thermoplastic liquid crystal polymer) that can form an optically anisotropic molten phase and an amorphous polymer. It records that by adding a polyarylate resin to the thermoplastic liquid crystal polymer, the film formation stability in the blow molding method can be improved. Specifically, horizontal shaking of bubbles extruded from an annular die can be prevented, the displacement amount can be reduced, and stable film formation can be maintained.

[0008] Patent Document 2 is an invention relating to a liquid crystal polymer composition containing a liquid crystal polymer and a polyarylate resin, and describes that by blending a polyarylate resin into a liquid crystal polymer, the melt tension is increased, thereby achieving excellent film-forming properties in extrusion molding.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Laid-Open No. 2000-290512

[0012] Patent Document 2: Japanese Patent Application Laid-Open No. 2020-193261 Summary of the invention

[0013] Furthermore, thermoplastic liquid crystal polyester has a high tensile elastic modulus and a low elongation at break, and therefore has high rigidity. After being formed into a film by blow extrusion molding, the film is prone to wrinkles and sagging, and a smooth film is difficult to obtain.

[0014] For example, in the blow extrusion molding method, a molten resin is extruded into a bubble shape from an annular slit, and air or an inert gas is blown into the bubble formed by the molten resin from the inside, thereby expanding and stretching the bubble in the MD direction and the TD direction, and the expanded and stretched bubble is brought into contact with a pair of stabilizing plates inclined so that the downstream sides in the MD direction are close to each other, and is slowly folded into a flat shape and guided to a pinch roller, and the bubble is folded into a plane shape by a pair of pinch rollers. In the process of bringing a cylindrical bubble into contact with the stabilizing plate and folding it into a flat shape by the pinch rollers, the bubble located at the center of the stabilizing plate and the bubble located at both ends of the stabilizing plate have different geometrical straight-line distances from the position where the bubble directly contacts the stabilizing plate to the pinch rollers. Therefore, when the rigidity of the resin is high, the film cannot be deformed when it is clamped in a plane shape between the pinch rollers, and the film produces slack or wrinkles in the MD direction (longitudinal wrinkles).

[0015] Therefore, when forming a thermoplastic liquid crystal polyester film by blow extrusion molding, it is effective to control the resin temperature of the bubbles when the bubbles are folded into a flat shape between the pinch rolls to be near the softening point at which the film is easily deformed, thereby suppressing the generation of slack and longitudinal wrinkles on the film. On the other hand, when the resin temperature of the bubbles is controlled to be near the softening point before the pinch roll position, a new problem arises, that is, the sliding property of the bubbles near the softening point is insufficient, and the friction between the bubbles and the stabilizing plate causes crescent-shaped wrinkles (transverse wrinkles) in the TD direction of the bubbles, making it difficult to form a smooth film.

[0016] The present invention has been made in view of the above problems, and its object is to provide a liquid crystal polyester resin composition which can suppress film sagging and wrinkle generation during extrusion molding such as blow extrusion molding and can form a stable film having excellent mechanical properties, electrical properties and heat resistance.

[0017] The present inventors have conducted intensive research on a resin composition that can stably form a film while maintaining the mechanical properties, electrical properties, heat resistance, etc. possessed by a thermoplastic liquid crystal polyester and suppressing film relaxation and wrinkle generation. As a result, they found that by adding an amorphous copolyester having a glass transition temperature of 80 to 200°C to a thermoplastic liquid crystal polyester, film relaxation and wrinkle generation can be suppressed in extrusion molding such as blow extrusion film forming, and a stable film can be formed, thereby completing the present invention.

[0018] According to the present invention, there is provided:

[0019] (1) A liquid crystal polyester resin composition, characterized in that it comprises a thermoplastic liquid crystal polyester (A) and an amorphous copolyester (B), wherein the glass transition temperature of the amorphous copolyester (B) is 80° C. or higher and 200° C. or lower, and the mixing ratio of the thermoplastic liquid crystal polyester (A) to the amorphous copolyester is (A): (B) = 50-99.5 wt %: 0.5-50 wt %,

[0020] (2) The liquid crystal polyester resin composition according to (1), characterized in that the thermoplastic liquid crystal polyester (A) contains at least one selected from the group consisting of constituent units derived from p-hydroxybenzoic acid and constituent units derived from 6-hydroxy-2-naphthoic acid,

[0021] (3) The liquid crystal polyester resin composition according to (1), characterized in that the amorphous copolyester (B) comprises a constituent unit derived from a terephthalic acid monomer and a constituent unit derived from 1,4-cyclohexanedimethanol,

[0022] (4) The liquid crystal polyester resin composition according to (1), characterized in that the amorphous copolyester (B) comprises constituent units derived from terephthalic acid monomers, constituent units derived from 1,4-cyclohexanedimethanol and constituent units derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol,

[0023] (5) The liquid crystal polyester resin composition according to (1), wherein the melting point of the thermoplastic liquid crystal polyester (A) is 250° C. or higher,

[0024] (6) The liquid crystal polyester resin composition according to (1), characterized in that the resin composition is used for blow extrusion molding,

[0025] (7) A liquid crystal polyester film, characterized in that it is formed from the resin composition described in any one of (1) to (6),

[0026] (8) A metal laminate film, characterized in that a metal layer is laminated on one or both sides of the liquid crystal polyester film described in (7),

[0027] (9) A circuit board comprising at least one conductive layer and the liquid crystal polyester film according to (7).

[0028] The liquid crystal polyester resin composition of the present invention can reduce the dependence of the melt viscosity of the resin composition on temperature and shear stress by containing an amorphous copolyester with a glass transition temperature of 80 to 200°C. Therefore, when forming a film in extrusion molding such as blow extrusion molding, the horizontal shaking of the bubbles extruded from the die head can be suppressed, and the opening of the bubbles can be suppressed, so that the film can be stably formed. In addition, the sliding property of the resin composition near the softening point can be improved. Therefore, in extrusion molding such as blow extrusion molding, wrinkles caused by friction with a stabilizing plate can be suppressed, thereby obtaining a smooth film without slack and wrinkles. In addition, the film forming processability can also be improved, and the excellent mechanical properties, electrical properties, and heat resistance of the thermoplastic liquid crystal polyester can be maintained. As a result, the liquid crystal polyester film formed by the liquid crystal polyester resin composition of the present invention and the metal laminate film obtained by laminating the liquid crystal polyester film with a metal layer have excellent mechanical properties, electrical properties, and reflow solderability, and can be used for laminated boards for circuit boards suitable for high-speed communication purposes. DETAILED DESCRIPTION

[0029] Hereinafter, the present invention will be described in detail. It should be noted that the present invention is not limited to the following forms, and various forms can be adopted within the scope of achieving the effects of the present invention.

[0030] [Liquid Crystal Polyester Resin Composition]

[0031] The liquid crystal polyester resin composition of the present invention is composed of a resin composition comprising a thermoplastic liquid crystal polyester (A) and an amorphous copolyester (B). By blending an amorphous copolyester (B) having a glass transition temperature of 80°C or more and 200°C or less, a smooth film can be stably formed in extrusion molding such as blown film. The reason has not yet been determined, but it is speculated as follows: Since the melt viscosity of the resin composition is less dependent on temperature and shear stress, the horizontal shaking of bubbles extruded from the die head and the opening of bubbles can be suppressed in extrusion molding such as blow extrusion molding, thereby stably forming a film. In addition, it is also speculated as follows: by blending an amorphous copolyester (B) having a glass transition temperature of 80°C or more and 200°C or less, the sliding property of the resin composition near the softening point is improved, so that in extrusion molding such as blow extrusion molding, the friction with the stabilizing plate can be reduced, and a smooth film without sag and wrinkles can be obtained.

[0032] [Thermoplastic liquid crystal polyester (A)]

[0033] The thermoplastic liquid crystal polyester (A) used in the present invention is a liquid crystal polyester showing melt anisotropy (a polyester that can form an optically anisotropic melt phase). The property of melt anisotropy can be confirmed by a conventional polarization inspection method using crossed polarizers. Specifically, melt anisotropy can be confirmed by using a polarizing microscope (manufactured by Olympus Corporation, etc.), melting a sample placed in a melting point meter (manufactured by LINKAM, etc.), and observing at a magnification of 150 times under a nitrogen atmosphere. A liquid crystal resin that shows optical anisotropy when melted is optically anisotropic and is light-transmissive after being inserted between crossed polarizers. When the sample is optically anisotropic, polarized light will be transmitted even in a molten static liquid state, for example.

[0034] The chemical composition of the thermoplastic liquid crystal polyester (A) is not particularly limited as long as it is a liquid crystal polyester that can be melt-formed, and examples thereof include thermoplastic liquid crystal polyesters having at least one repeating unit selected from the group consisting of aromatic hydroxycarboxylic acids, aromatic or aliphatic diols, aromatic or aliphatic dicarboxylic acids, aromatic diamines, aromatic hydroxylamines and aromatic aminocarboxylic acids.

[0035] As aromatic hydroxycarboxylic acids, p-hydroxybenzoic acid, m-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid and 4-(4-hydroxyphenyl)benzoic acid can be mentioned. These compounds may have substituents such as halogen atoms, lower alkyl groups and phenyl groups. Among them, p-hydroxybenzoic acid or 6-hydroxy-2-naphthoic acid is preferred. As aromatic or aliphatic diols, aromatic diols are preferred. As aromatic diols, hydroquinone, 4,4'-dihydroxybiphenyl, 3,3'-dimethyl-1,1'-biphenyl-4,4'-diol and their acyl compounds can be mentioned, preferably hydroquinone or 4,4'-dihydroxybiphenyl. As aromatic or aliphatic dicarboxylic acids, aromatic dicarboxylic acids are preferred. As aromatic dicarboxylic acids, terephthalic acid, isophthalic acid and 2,6-naphthalene dicarboxylic acid can be mentioned, preferably terephthalic acid. Examples of the aromatic diamine, aromatic hydroxyamine, and aromatic aminocarboxylic acid include p-phenylenediamine, 4-aminophenol, and 4-aminobenzoic acid.

[0036] The thermoplastic liquid crystal polyester (A) preferably has at least one selected from the group consisting of repeating units represented by the following formulae (1) to (3).

[0037] -O-Ar1-CO-(1)

[0038] -CO-Ar2-CO-(2)-X-Ar3-Y-(3)

[0039] In the formula (1), Ar1 represents a phenylene group, a naphthylene group or a biphenylene group.

[0040] In the formula (2), Ar2 represents a phenylene group, a naphthylene group, a biphenylene group or a group represented by the following formula (4).

[0041] In the formula (3), Ar3 represents a phenylene group, a naphthylene group, a biphenylene group or a group represented by the following formula (4), and X and Y each independently represent an oxygen atom or an imino group.

[0042] -Ar4-Z-Ar5-(4)

[0043] In formula (4), Ar4 and Ar5 each independently represent a phenylene group or a naphthylene group, and Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group or an alkylene group.

[0044] The phenylene group, the naphthylene group, and the biphenylene group may have a substituent selected from the group consisting of a halogen atom, an alkyl group, and an aryl group.

[0045] Among them, the thermoplastic liquid crystal polyester (A) preferably has at least one selected from the group consisting of repeating units of an aromatic hydroxycarboxylic acid represented by the above formula (1), repeating units derived from an aromatic diol represented by the above formula (3) in which both X and Y are oxygen atoms, and repeating units derived from an aromatic dicarboxylic acid represented by the above formula (2).

[0046] In addition, as a thermoplastic liquid crystal polyester (A), it is preferred to have a constituent unit derived from an aromatic hydroxycarboxylic acid, more preferably to have at least one selected from the group consisting of a constituent unit derived from p-hydroxybenzoic acid and a constituent unit derived from 6-hydroxy-2-naphthoic acid, and further preferably to have a constituent unit derived from p-hydroxybenzoic acid and a constituent unit derived from 6-hydroxy-2-naphthoic acid.

[0047] In other preferred embodiments, as a thermoplastic liquid crystal polyester (A), it is more preferred that it has at least one selected from the group consisting of a constituent unit derived from 6-hydroxy-2-naphthoic acid, a constituent unit derived from an aromatic diol, a constituent unit derived from terephthalic acid and a constituent unit derived from 2,6-naphthalenedicarboxylic acid, and it is further preferred that it has all of a constituent unit derived from 6-hydroxy-2-naphthoic acid, a constituent unit derived from an aromatic diol, a constituent unit derived from terephthalic acid and a constituent unit derived from 2,6-naphthalenedicarboxylic acid.

[0048] The synthesis method of the thermoplastic liquid crystal polyester (A) is not particularly limited, and can be synthesized by polymerizing the above-mentioned compounds by known methods such as melt polymerization, solid phase polymerization, solution polymerization and slurry polymerization. As a thermoplastic liquid crystal polyester (A), a commercially available product can also be used. As a commercially available product of a thermoplastic liquid crystal polyester, for example: "LAPEROS" manufactured by POLYPLASTICS, "Vectra" manufactured by Celanese, "UENO LCP" manufactured by Ueno Pharmaceutical, "SUMIKASUPER LCP" manufactured by Sumitomo Chemical, "Xydar" manufactured by ENEOS, and "Siveras" manufactured by Toray Industries, Inc. can be cited. It should be noted that the thermoplastic liquid crystal polyester (A) can be a cross-linking agent or a compatible component (reactive compatibility agent) as an optional component to form a chemical bond.

[0049] Thermoplastic liquid crystal polyester (A) preferably has a melting point of 250°C or more. When the melting point is lower than 250°C, the reflow soldering property is poor, so when used for printed circuit boards and the like, the processing method is limited. The melting point of the thermoplastic liquid crystal polyester (A) is not particularly limited, but from the viewpoints of heat resistance and molding processability, for example, it is preferably 400°C or less, more preferably 350°C or less, further preferably 330°C or less, and particularly preferably 300°C or less. The lower limit of the melting point is more preferably 260°C or more, and more preferably 270°C or more. It should be noted that as the melting point of the thermoplastic liquid crystal polyester (A), a differential scanning calorimeter (DSC) is used to heat the sample at a rate of 10°C / min to completely melt it, and then the melt is cooled to 30°C at a rate of 10°C / min, and the position of the endothermic peak that appears after heating at a rate of 10°C / min is taken as the melting point.

[0050] [Amorphous copolyester (B)]

[0051] The amorphous copolyester (B) used in the present invention is a polycondensate of a polycarboxylic acid and a polyol, and does not have a clear endothermic peak in thermal analysis measurement using differential scanning calorimetry (DSC). For example, in thermal analysis measurement using DSC, it only has a step-like endothermic change, is solid at room temperature, and undergoes thermal plasticization at a temperature above the glass transition temperature.

[0052] The amorphous copolyester (B) preferably contains constituent units derived from terephthalic acid monomers and constituent units derived from 1,4-cyclohexanedimethanol. The terephthalic acid monomers are terephthalic acid or derivatives of terephthalic acid. As derivatives of terephthalic acid, for example, halides, esters, half esters, salts, half salts, anhydrides, mixed anhydrides, and mixtures thereof of terephthalic acid can be cited. As derivatives of terephthalic acid, for example, dialkyl esters and diaryl esters of terephthalic acid can be cited, and specific examples thereof include dimethyl terephthalate (DMT) and diethyl terephthalate.

[0053] The amorphous copolyester (B) may also contain constituent units from other monomers. In one embodiment, constituent units from dicarboxylic acids (other dicarboxylic acids) other than terephthalic acid monomers are also included. As other dicarboxylic acids, for example, cyclohexane dicarboxylic acid, isophthalic acid, naphthalene dicarboxylic acid, diphenyl dicarboxylic acid, stilbene dicarboxylic acid, etc. can be cited. As cyclohexane dicarboxylic acids, 1,3- and / or 1,4-cyclohexane dicarboxylic acids, etc. can be cited. In the case where the amorphous copolyester (B) contains constituent units from other dicarboxylic acids, the content ratio of the constituent units from terephthalic acid monomers is preferably 40 mol% or more relative to the total amount of dicarboxylic acids (the total amount of constituent units from terephthalic acid monomers and constituent units from other dicarboxylic acids), more preferably 40 mol% to 90 mol%, and further preferably 50 mol% to 85 mol%.

[0054] The amorphous copolyester (B) may also contain constituent units from diols (other diols) other than 1,4-cyclohexanedimethanol. As other diols, for example, aliphatic or alicyclic diols (preferably having 2 to 20 carbon atoms) may be mentioned. As other diols, for example, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, neopentyl glycol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, etc. may be mentioned. In one embodiment, the amorphous copolyester (B) further contains constituent units from 2,2,4,4-tetramethyl-1,3-cyclobutanediol. When the amorphous copolyester (B) contains a constituent unit derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD), the content ratio of the constituent unit derived from 1,4-cyclohexanedimethanol (CHDM) is preferably 10 mol% to 90 mol% relative to the total of the constituent units derived from TMCD and the constituent units derived from CHDM, more preferably 20 mol% to 85 mol%, and further preferably 30 mol% to 80 mol%. In addition, the content ratio of the constituent unit derived from TMCD is preferably 10 mol% to 90 mol% relative to the total of the constituent units derived from TMCD and the constituent units derived from CHDM, more preferably 15 mol% to 80 mol%, and further preferably 20 mol% to 70 mol%.

[0055] The glass transition temperature (Tg) of the amorphous copolyester (B) is 80°C or higher and 200°C or lower, preferably 85°C or higher and 180°C or lower, more preferably 90°C or higher and 160°C or lower, further preferably 95°C or higher and 150°C or lower, and particularly preferably 100°C or higher and 140°C or lower. It should be noted that the glass transition temperature can be measured by a conventionally known method, for example, it can be obtained by differential scanning calorimetry based on JISK-7121:2012. In addition, when the glass transition temperature has a value published by a manufacturer, the published value of the manufacturer can be used.

[0056] The liquid crystal polyester resin composition of the present invention comprises the above-mentioned thermoplastic liquid crystal polyester (A) and amorphous copolyester (B) in a ratio of (A): (B) = 50 to 99.5% by weight: 0.5 to 50% by weight. Preferably, (A): (B) = 70 to 99% by weight: 1 to 30% by weight, more preferably (A): (B) = 80 to 98.5% by weight: 1.5 to 20% by weight, further preferably (A): (B) = 85 to 98% by weight: 2 to 15% by weight, and particularly preferably (A): (B) = 90 to 97.5% by weight: 2.5 to 10% by weight. When the amount of amorphous copolyester (B) is less than the above range, there is no effect of reducing the dependence of the melt viscosity of the liquid crystal polyester resin composition on temperature and shear stress, and there is no effect of improving the slipperiness of the resin composition near the softening point, so it is difficult to obtain a smooth film by film forming by blow extrusion molding. When the amount of the amorphous copolyester (B) is greater than the above range, the heat resistance and mechanical properties of the liquid crystal polyester film formed from the liquid crystal polyester resin composition may be reduced.

[0057] The liquid crystal polyester resin composition of the present invention may include other resin components other than the above-mentioned thermoplastic liquid crystal polyester (A) and amorphous copolyester (B) within the range that does not impair the effect of the present invention. As other resin components, thermoplastic resins such as polyarylate, polyphenylene sulfide, polyphenylene ether, polyetheretherketone, polyetherimide, cycloolefin polymer, polyamide, polyamideimide, polyimide, epoxy-containing olefin copolymer, styrene resin, copolyester elastomer, etc. can be cited. In addition, the liquid crystal polyester resin composition of the present invention may include additives such as compatibilizers, lubricants, antioxidants, and fillers. It should be noted that, in the case where the liquid crystal polyester resin composition of the present invention includes other components, it is preferably included as the main component. The main component means that the composition ratio in the components constituting the resin composition is 50% by weight or more, preferably 60% by weight or more, more preferably 80% by weight or more, further preferably 90% by weight or more, and particularly preferably 95% by weight or more.

[0058] [Method for producing liquid crystal polyester film]

[0059] In the present invention, a film formed by the above-mentioned resin composition and a method for manufacturing the film are also proposed. The liquid crystal polyester film of the present invention can be obtained by blending and forming a film of the above-mentioned thermoplastic liquid crystal polyester (A) and amorphous copolyester (B) by a known method. It should be noted that, as the resin composition of the present invention, when the proportion of the amorphous copolyester (B) decreases, in order to provide a stable mixing state, it is preferably melt-mixed and granulated in advance before film formation.

[0060] The equipment used for melt kneading is not particularly limited, and examples thereof include various known extruders such as a batch mixer, a kneader, a co-kneader, a Banbury mixer, a roll mill, and a single-screw or twin-screw extruder. Among them, single-screw extruders and twin-screw extruders are preferably used from the perspective of excellent kneading capacity and productivity.

[0061] In the resin composition of the present invention, by adding the amorphous copolyester (B), the rapid decrease or change of the melt viscosity of the resin composition due to temperature and shear stress can be suppressed, thereby improving the film forming processability of the film formed by blow extrusion. In addition, by blending the amorphous copolyester (B), the sliding property of the resin composition near the softening point is improved, and in extrusion molding such as blow extrusion molding, the generation of wrinkles due to friction with a stabilizing plate can be suppressed, and a smooth film without sag and wrinkles can be obtained.

[0062] As blow extrusion molding, for example, the following method can be cited: the above-mentioned resin composition is provided to a melt extruder having a die head with an annular slit, and the resin composition in a molten state is extruded from the annular slit of the extruder from above or below in a bubble shape, and air or an inert gas is blown into the inside of the bubble composed of the molten resin composition, thereby expanding and stretching the bubble in a direction (TD direction) at right angles to the flow direction (MD direction) to obtain a film. The barrel temperature of the melt extruder is usually 260~400°C, preferably 280~380°C. The interval of the annular slit is usually 0.1~5mm, preferably 0.2~2mm. The diameter of the annular slit is usually 20~1000mm, preferably 25~600mm.

[0063] In blow extrusion molding, the blow ratio is preferably 1.5 or more, more preferably 2.0 or more, further preferably 4.0 or more, and particularly preferably 4.5 or more. The upper limit of the blow ratio is not particularly limited, for example, the blow ratio is 10 or less. In addition, the draft ratio is preferably 1.5 or more and 20 or less, more preferably 1.5 or more and 10 or less. Among them, the blow ratio is the stretching ratio in the TD direction, and the draft ratio is the stretching ratio in the MD direction. When the blow ratio and the draft ratio are in the above range, the anisotropy of the tensile modulus and the tensile strength of the obtained film (the difference between the MD direction and the TD direction) can be improved. However, in the blow extrusion molding of the liquid crystal polyester resin composition, the shape of the bubbles composed of the resin composition in the molten state is increased in order to improve the anisotropy of the film. The tendency to remain unstable, therefore, vibration and opening of bubbles are easily generated. In contrast, the resin composition of the present invention, by adding an amorphous copolyester (B), can reduce the rapid decrease or change in the melt viscosity of the resin composition caused by temperature and shear stress, so that even if the blow-up ratio is greater than 4.0, the formation of pores on the bubbles can be suppressed, the anisotropy of the film can be improved, and the film can be stably formed.

[0064] The thickness of the liquid crystal polyester film of the present invention is not particularly limited, and is, for example, 0.5 μm to 1000 μm inclusive. Taking into account operability and productivity during melt extrusion, the thickness is preferably 5 μm to 500 μm inclusive, more preferably 10 μm to 300 μm inclusive, and further preferably 20 μm to 200 μm inclusive.

[0065] The tensile strength of the liquid crystal polyester film of the present invention in the flow direction (MD direction) and the width direction (TD direction) is preferably 180MPa or more. The tensile strength is more preferably 200MPa or more, and more preferably 220MPa or more. The upper limit of the tensile strength is not particularly limited, for example, preferably 500MPa or less, more preferably 400MPa or less, and more preferably 350MPa or less. If the tensile strength is within the above range, the operability when processed into a laminate suitable for a circuit board for high-speed communication purposes is excellent, and the missing and cracking generated at the end of the film can be suppressed.

[0066] The liquid crystal polyester film of the present invention preferably has low anisotropy in the flow direction (MD direction) and the width direction (TD direction). In detail, the tensile strength F(TD) in the width direction of the film relative to the tensile strength F(MD) in the flow direction of the film (i.e., F(TD) / F(MD)) is preferably 0.5 or more and 1.5 or less, more preferably 0.75 or more and 1.25 or less, further preferably 0.85 or more and 1.15 or less, and particularly preferably 0.90 or more and 1.10 or less. If the tensile strength F(TD) in the width direction of the film relative to the tensile strength F(MD) in the flow direction of the film is within the above range, the anisotropy of the mechanical properties and electrical properties of the film is small, and it can be applied to laminates for circuit boards suitable for high-speed communication purposes.

[0067] The dielectric loss tangent of the liquid crystal polyester film of the present invention is preferably 0.0025 or less, the dielectric loss tangent is more preferably 0.0024 or less, further preferably 0.0022 or less, and particularly preferably 0.0020 or less. In addition, the relative dielectric constant of the liquid crystal polyester film of the present invention is preferably 2.0 to 4.0. The relative dielectric constant is further preferably 2.5 to 3.9, more preferably 2.6 to 3.8, and further preferably 2.8 to 3.8. Dielectric properties including the standard dielectric loss tangent and the relative dielectric constant can be measured by the cavity resonator perturbation method.

[0068] The liquid crystal polyester film of the present invention can be further heat treated to relax the orientation of the molecular chains and improve the film dimensional stability. The heat treatment can be performed by a conventionally known method, for example, contact heat treatment, non-contact heat treatment, etc., and the type of heat treatment is not particularly limited.

[0069] [Metallic Laminated Film]

[0070] The liquid crystal polyester film of the present invention may be laminated with a metal layer to form a metal laminate film. When the metal layer is laminated, the surface of the liquid crystal polyester film laminated with the metal layer may be subjected to corona discharge treatment, ultraviolet irradiation treatment or plasma treatment in order to improve the adhesive force.

[0071] As a method for laminating a metal layer on the liquid crystal polyester film of the present invention, for example: (1) a method of attaching the liquid crystal polyester film to a metal foil by heating and pressing, (2) a method of laminating the liquid crystal polyester film and the metal foil by an adhesive, and (3) a method of forming a metal layer on the liquid crystal polyester film by vapor deposition. Among them, the lamination method (1) is a method of pressing the liquid crystal polyester film with the metal foil near the flow starting temperature using a punch or a heating roller, which can be easily implemented and is therefore recommended. As an adhesive used in the lamination method (2), for example: hot melt adhesives and polyurethane adhesives can be mentioned. Among them, ethylene copolymers containing epoxy groups are preferably used as adhesives. As a lamination method (3), for example: ion beam sputtering, high-frequency sputtering, DC magnetron sputtering, glow discharge method can be mentioned. Among them, high-frequency sputtering is preferably used.

[0072] As the metal used for the metal layer, for example, gold, silver, copper, copper alloy, nickel, nickel alloy, aluminum, aluminum alloy, iron, iron alloy, etc. can be cited. In lead frame and circuit board applications, copper is preferred, and in capacitor applications, aluminum is preferred. As the structure of the metal laminated film thus obtained, for example, a two-layer structure of a liquid crystal polyester film and a metal layer, a three-layer structure formed by laminating metal layers on both sides of the liquid crystal polyester film, and a five-layer structure formed by alternately laminating liquid crystal polyester films and metal layers can be cited. It should be noted that in order to achieve high-intensity display, the laminate can be heat-treated as needed. The thickness of the metal layer is not particularly limited, for example, preferably 1.5~1000μm, more preferably 2~500μm, further preferably 5~150μm, and particularly preferably 7~100μm. When it is thinner than this range, the mechanical strength is poor, and when it is thicker than the above range, the operability and processability are poor.

[0073] The circuit board of the present invention comprises at least one conductor layer and at least one insulator (or dielectric) layer. As long as the liquid crystal polyester film of the present invention is used as an insulator (or dielectric), its form is not particularly limited and it can be used as various high-frequency circuit boards in a known or conventional manner. In addition, the circuit board can be a circuit board (or a semiconductor element mounting substrate) equipped with a semiconductor element (e.g., an IC chip).

[0074] The conductor layer of the circuit board used in the present invention is formed of at least a conductive metal, and a circuit pattern is formed on the conductor layer using a known circuit processing method. The conductor forming the conductor layer can be various conductive metals, such as gold, silver, copper, iron, nickel, aluminum, or alloys thereof. In addition, the circuit pattern can be formed on the metal layer portion of the above-mentioned metal laminate film.

[0075] Example

[0076] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to the following examples.

[0077] As the resin used in Examples and Comparative Examples, the following were used.

[0078] (Thermoplastic Liquid Crystal Polyester)

[0079] ・LCP (1): A thermoplastic liquid crystal polyester composed of a structural unit derived from p-hydroxybenzoic acid and a structural unit derived from 6-hydroxy-2-naphthoic acid (LAPEROS A950RX manufactured by Polyplastics Corporation, melting point: 280°C, softening point: 266°C)

[0080] ・LCP (2): A thermoplastic liquid crystal polyester composed of a structural unit derived from p-hydroxybenzoic acid, a structural unit derived from 6-hydroxy-2-naphthoic acid, and a structural unit derived from terephthalic acid (LAPEROS C950RX manufactured by Polyplastics Corporation, melting point: 320°C, softening point: 303°C)

[0081] (Amorphous polymer)

[0082] ・Amorphous polymer (1): Amorphous copolyester containing a constituent unit derived from terephthalic acid, a constituent unit derived from 1,4-cyclohexanedimethanol, and a constituent unit derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol (Traitan TX2001 manufactured by Eastman Chemical Co., Ltd., Tg: 116°C)

[0083] ・Amorphous polymer (2): Amorphous copolyester containing a constituent unit derived from terephthalic acid, a constituent unit derived from 1,4-cyclohexanedimethanol, and a constituent unit derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol (Traitan TX1001 manufactured by Eastman Chemical Co., Ltd., Tg: 108°C)

[0084] ・Amorphous polymer (3): Amorphous copolyester containing a constituent unit derived from terephthalic acid, a constituent unit derived from 1,4-cyclohexanedimethanol, and a constituent unit derived from ethylene glycol (PETGGN001 manufactured by Eastman Chemical Co., Ltd., Tg: 90°C)

[0085] ・Amorphous polymer (4): Amorphous copolyester containing a constituent unit derived from terephthalic acid, a constituent unit derived from 1,4-cyclohexanedimethanol, and a constituent unit derived from ethylene glycol (PCTGDN011 manufactured by Eastman Chemical Co., Ltd., Tg: 90°C)

[0086] ・Amorphous polymer (5): Amorphous copolyester containing a structural unit derived from terephthalic acid, a structural unit derived from 1,4-cyclohexanedimethanol, and a structural unit derived from isophthalic acid (PCTAAN004 manufactured by Eastman Chemical Co., Ltd., Tg: 90°C)

[0087] ・Amorphous polymer (6): polyarylate resin (U polymer U-1 manufactured by Unitika Co., Ltd.

[0088] 00, Tg: 193℃)

[0089] ・Amorphous polymer (7): Polysulfone resin (Ultrason S301 manufactured by BASF

[0090] 0. Tg: 187℃)

[0091] ・Amorphous polymer (8): Polysulfone resin (Udel P-1700NT manufactured by Solvay

[0092] 11. Tg: 185℃)

[0093] ・Amorphous polymer (9): Polymer alloy of polyetherimide resin and polyethylene terephthalate resin (ULTEM DU319 manufactured by SABIC, Tg: 185°C)

[0094] ・Amorphous polymer (10): Polycarbonate resin (LEXAN XT3 manufactured by SABIC

[0095] 143T, Tg: 175℃)

[0096] ・Amorphous polymer (11): Polymer alloy of polyphenylene ether resin and polystyrene resin (NORYLEFN4230S manufactured by SABIC, Tg: 175°C)

[0097] ・Amorphous polymer (12): polymethyl methacrylate resin (ACRYPET VH001 manufactured by Mitsubishi Chemical Corporation, Tg: 100°C)

[0098] (additive)

[0099] ・Polyester elastomer: Block copolymer of polybutylene terephthalate and polybutylene glycol (PBT / PTMG)

[0100] It should be noted that according to JIS K7196 (1991), a sample with a width of 5 mm, a length of 5 mm, and a thickness of 0.05 mm was prepared, and a thermochemical mechanical analyzer (manufactured by SII NanoTechnology, model: TMA / SS7100) was used as a measuring device. Five sheets were stacked under a nitrogen atmosphere, a heating rate of 5°C / min, and a temperature range of 30°C to 350°C. A load of 50 gf was applied, and a transparent quartz pin (diameter of the tip φ0.5 mm) was inserted into the sample thus obtained to measure the softening point. The glass transition temperature used the catalog value of the manufacturer.

[0101] (1) Manufacturing of molded products by injection molding

[0102] After premixing the thermoplastic liquid crystal polyester resin composition according to the ratio described in Table 1, an injection molding machine (Hand Truder M-1, Toyo Seiki Seisakusho Co., Ltd.) was used to extrude at a barrel temperature of 300°C to obtain a strip test piece (length 82 mm, width 10 mm, thickness 4 mm). The obtained strip test piece was visually observed for the presence or absence of foaming and the appearance. The evaluation results are shown in Table 1.

[0103] [Table 1]

[0104]

[0105] As a result of the basic evaluation of injection molded products, the resin composition of Reference Example 7, which contains a polycarbonate resin as an amorphous polymer, showed that foaming occurred during injection molding, and the obtained injection molded products turned yellow and had a poor appearance. In addition, the resin composition of Reference Example 8, which contains a polymer alloy of a polyphenylene ether resin and a polystyrene resin as an amorphous polymer, and the resin composition of Reference Example 9, which contains a polymethyl methacrylate resin as an amorphous polymer, showed that foaming occurred during injection molding. In the evaluation of injection molding, no problems were found in the processability and appearance of the resin compositions of Reference Examples 1 to 6.

[0106] (2) Film manufacturing using blow molding

[0107] After premixing the thermoplastic liquid crystal polyester resin composition according to the ratio described in Table 2, it was heated and kneaded by a single screw extruder, and melt-extruded into a bubble shape from an annular blow die (diameter 25 mm) at a discharge rate of 3 kg / h, and the bubble was stretched under the conditions of draft ratio = 2 and blow ratio = 5, and a liquid crystal polyester film with a thickness of 50 μm was obtained by blow extrusion molding. The resin temperature of the bubble during film formation was controlled in such a way that the softening point between the contact position with the stabilizing plate and the pinch rollers reached -40°C or above. The film forming properties and physical properties of the film obtained by the following evaluation method are shown in Table 2.

[0108] (Film-forming property: Bubble stability)

[0109] When a film was formed by the blow extrusion molding method, horizontal shaking of the end of the bubble in the TD direction at the position where the bubble in the molten state had completed expansion was visually evaluated according to the following criteria.

[0110] ○: The bubbles hardly shake;

[0111] ○△: The bubble sways slightly repeatedly along the TD direction, which is unstable;

[0112] △: The bubbles repeatedly and greatly oscillate in the TD direction and are unstable.

[0113] (Film-forming property: opening of bubbles)

[0114] When a film was formed by the blow extrusion molding method, the appearance of bubbles composed of the molten resin extruded from the die was visually evaluated according to the following criteria.

[0115] ○: No opening on the bubble;

[0116] ○△: Small openings are sparsely generated on the bubbles;

[0117] △: Many small openings are generated on the bubbles (the exhaust inside the bubbles affects the shape of the bubbles);

[0118] ×: A large number of openings are generated on the bubbles, and continuous film formation is impossible

[0119] (film forming property: wrinkles of the film);

[0120] The obtained film was visually evaluated for sag and wrinkles in the TD direction (transverse wrinkles) according to the following criteria.

[0121] ○: No sagging or wrinkles were observed on the film;

[0122] ○△: Faint wrinkles are visible on the film;

[0123] △: Multiple fuzzy wrinkles and looseness can be seen on the film;

[0124] △×: Multiple fuzzy wrinkles and clear wrinkles are visible on the film, and relaxation is also visible;

[0125] ×: A number of clear wrinkles were observed on the film, and sagging was observed.

[0126] (Physical properties: tensile strength)

[0127] According to ASTM D882, an autograph AGS-500NX (manufactured by Shimadzu Corporation) was used, with a tensile speed of 12.5 mm / min and a distance between the clamps of 125 mm, to measure a sample cut into a size of 190 mm × 15 mm. The measurement temperature was 23° C. It should be noted that both the flow direction (MD direction) and the width direction (TD direction) of the film were measured.

[0128] (Physical properties: relative dielectric constant, dielectric loss tangent)

[0129] The relative dielectric constant and dielectric loss tangent in the 10 GHz frequency band were measured using a cavity resonator (10 GHz resonator manufactured by AET) and a network analyzer (MS46122B manufactured by Anritsu) at a temperature of 23°C and a humidity of 65% RH. It should be noted that both the flow direction (MD direction) and the width direction (TD direction) of the film were measured.

[0130] [Table 2]

[0131]

[0132] As shown in Table 2, in the liquid crystal polyester films of Examples 1 to 12 containing amorphous copolyesters having a glass transition temperature of 80 to 200° C., the following results were shown: the opening of bubbles extruded from the die and horizontal shaking can be suppressed, and a film can be stably formed, and a smooth film without sag and wrinkles can be obtained. In addition, in the liquid crystal polyester films of Examples 1 to 12, the following results were shown: the film forming processability was improved, and the excellent mechanical properties and electrical properties of the thermoplastic liquid crystal polyester were maintained.

[0133] On the other hand, in the liquid crystal polyester film of Comparative Example 1 containing polyarylate as the amorphous polymer, although it showed a certain effect in terms of the stability of bubbles and the opening of bubbles, it showed that the film was loose and had lateral wrinkles, and a smooth film could not be obtained. This result shows that the addition of an amorphous copolyester with a glass transition temperature of 80 to 200°C is important for improving the sliding property of bubbles near the softening point.

[0134] The resin compositions of Comparative Examples 2 to 4, which included a polymer alloy of a polysulfone resin, a polyetherimide resin, and a polyethylene terephthalate resin as an amorphous polymer, showed some effects in terms of the stability of the bubbles and the opening of the bubbles, but the films showed many sags and transverse wrinkles, and only films that were difficult to evaluate physical properties were obtained. In addition, in Reference Example 10, which was formed from only the thermoplastic liquid crystal polyester, many openings were generated on the bubbles, and a film could not be continuously formed, and no film was obtained.

[0135] Industrial Applicability

[0136] As described above, the liquid crystal polyester film obtained by the present invention exerts its excellent mechanical properties, electrical properties, dimensional stability and heat resistance, and is used for electrical insulation of motors and transformers and element formation films of flexible solar cells, etc. It can also be used in acoustic fields such as surface protection films and vibration plates.

[0137] The metal laminate film of the present invention can also be used for circuit boards, capacitors, electromagnetic shielding materials, etc. The circuit board of the present invention can be used for various transmission lines and antennas (eg, microwave or millimeter wave antennas), and also for antenna devices in which antennas and transmission lines are integrated.

Claims

1. A liquid crystal polyester resin composition, characterized in that: It comprises a thermoplastic liquid crystal polyester (A) and an amorphous copolyester (B), wherein the glass transition temperature of the amorphous copolyester (B) is greater than 80°C and less than 200°C, and the mixing ratio of the thermoplastic liquid crystal polyester (A) to the amorphous copolyester is (A): (B) = 50~99.5 wt %: 0.5~50 wt %.

2. The liquid crystal polyester resin composition according to claim 1, characterized in that: The thermoplastic liquid crystal polyester (A) includes at least one selected from the group consisting of a constituent unit derived from p-hydroxybenzoic acid and a constituent unit derived from 6-hydroxy-2-naphthoic acid.

3. The liquid crystal polyester resin composition according to claim 1, characterized in that: The amorphous copolyester (B) includes a constituent unit derived from a terephthalic acid-based monomer and a constituent unit derived from 1,4-cyclohexanedimethanol.

4. The liquid crystal polyester resin composition according to claim 1, characterized in that: The amorphous copolyester (B) includes a constituent unit derived from a terephthalic acid-based monomer, a constituent unit derived from 1,4-cyclohexanedimethanol, and a constituent unit derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol.

5. The liquid crystal polyester resin composition according to claim 1, characterized in that: The melting point of the thermoplastic liquid crystal polyester (A) is 250° C. or higher.

6. The liquid crystal polyester resin composition according to claim 1, characterized in that: The resin composition is used for blow extrusion molding.

7. A liquid crystal polyester film, characterized in that: The method is formed from the resin composition according to any one of claims 1 to 6.

8. A metal laminate film, characterized in that: A metal layer is laminated on one or both surfaces of the liquid crystal polyester film according to claim 7 . 9 . A circuit board comprising at least one conductive layer and the liquid crystal polyester film according to claim 7 .

Citation Information

Patent Citations

  • Liquid crystal polymer composition

    JP2020193261A